ASYMPTOTIC BEHAVIOR OF THE WAVE EQUATION WITH BOUNDARY CONDITION OF NEWMANN TYPE, LOCALLY DISTRIBUTED - Pérez Salvatierra, Alfonso (2008)
In this note we shall study the asymptotic behavior of the wave equation with boundary condition of Newmann type, locally distributed. Using the Principle of the Unique Continuation, result studied by Ruiz (5) and applied to problems of asymptotic behavior by Zuazua (6).